Between Simón and Paulo: Legacies of Latin American Emancipatory Educations - Aguilera-Morales, Alcira (Revista Saberes Educativos, 2021)
The present article investigates some emancipatory educational legacies that we find in the thought of Simón Rodríguez and Paulo Freire. This seeks to contribute to the visibility of the Latin American pedagogical tradition. To do this, a documentary search was carried out on some of these authors’ works, which allowed us to identify three legacies. The first associates the emancipatory perspective with the origin of concern of critically reading the world, which arises from the review of one’s life experience. The second shows that emancipatory education requires the work of "invention", which requires knowing the order of injustice and inequality to risk other possibilities of education and society. Third, it is found that this emancipatory education is linked to the recognition of "one’s own", a principle associated with struggles from one’s own culture, language and history, and knowledge of territorialized needs and conditions of existence.